Packaging and storage of dehydrated, candied kamias (Averrhoa bilimbi Linn.) - Borlagdan, Doreen B.
This research was conducted with the main purpose of determining the storage and packaging requirements of dehydrated, candied kamias. The product was prepared according to the standard procedure developed by Avellaneda (1976) for pilot-scale production. Optimum sweating time was determined by storing the product in jars for two,three and four weeks. The optimum sweating time for the product was found to be two weeks. The sorption isotherm of the product which was determined by the Wink's weight equilibrium method, had a typical sigmoid shape. The critical moisture content of the product was found to be 23.20% (wet basis) or 30.21% (dry basis) and corresponds to an equilibrium relative humidity of 78.6%. based on these data, the maximum allowable WVTR requirement for a packaging material was calculated to be 1.3080 gm/m^2 - day at 90% RH and 28° - 30°C. Three packaging materials were selected on the basis of the WVTR values, costs and availability. They are: Cello/PE, Cello/Foil/PE and Paper/Foil/PE. Fifty grams of the product were packed in each of the packaging materials. These packages together with empty packaging materials were the equilibrium moisture content (Me) was determined. Moisture content (M) of the product at different storage times were computed. Values of log (Me - M) were then plotted versus storage time. The half-value period (HVP) for each packaging material at 38°C were determined from the slope of the curves. In this study, the shelf-life was determined by the HVP method. Results of the shelf-life tests showed that Cello/Foil/PE and Paper/Foil/PE laminates can provide the product with a shelf-life greater that the desired shelf-life of 360 days. However, between these two packaging materials, Cello/Foil/PE provides the product with a longer shelf-life. It is also cheaper packaging materia